2000
DOI: 10.1016/s0735-1097(00)00863-9
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term results after thrombolytic treatment of deep venous thrombosis

Abstract: Systemic thrombolytic treatment for acute DVT achieved a significantly better short- and long-term clinical outcome than conventional heparin/anticoagulation therapy but at the expense of a serious increase in major bleeding and pulmonary emboli. Given the inherent risks for such serious complications, systemic thrombolysis, although effective, should be used selectively in limb-threatening thrombotic situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(100 citation statements)
references
References 13 publications
3
95
0
2
Order By: Relevance
“…Selection criteria for identifying patients who might benefit from thrombolytic treatment are based on a subjective assessment of patient history. [5][6][7] Catheter-directed thrombolysis has reduced the rate of complications, but the time interval between the onset of symptoms and effective thrombolysis is still unclear. Several studies have shown that thrombolysis might be ineffective if administered 10 to 21 days after the onset of symptoms.…”
mentioning
confidence: 99%
“…Selection criteria for identifying patients who might benefit from thrombolytic treatment are based on a subjective assessment of patient history. [5][6][7] Catheter-directed thrombolysis has reduced the rate of complications, but the time interval between the onset of symptoms and effective thrombolysis is still unclear. Several studies have shown that thrombolysis might be ineffective if administered 10 to 21 days after the onset of symptoms.…”
mentioning
confidence: 99%
“…The stimulus can range from the exposure of subendothelial proteins, as in the case of tissue injury, to the development of turbulent blood flow through a narrowed blood vessel as in atherosclerosis. In the treatment of stroke or deep vein thrombus formation, the systemic administration of thrombolytic drugs, such as tissue plasminogen activator or streptokinase, has been the most successful and widely used (1). Thrombolytic drugs work by catalyzing the activation of plasmin (an enzyme that degrades fibrin clots) from its inactive circulating precursor plasminogen from plasma.…”
mentioning
confidence: 99%
“…Thrombin induces its plateletactivating effects mainly through a family of G protein-coupled protease-activated receptors (PARs) 1 ; these receptors are activated by a mechanism in which a protease creates a new amino terminus that functions as its own tethered ligand and thus results in intramolecular activation (4,5). Of the four known PARs, three (PAR-1, PAR-3 and PAR-4) are activated by thrombin.…”
mentioning
confidence: 99%
“…Thrombolytic therapy is an effective way to relieve early-stage thrombosis, and regional or systemic thrombolysis via a superficial vein has been proven effective. However, because large doses of drugs are required for systemic thrombolysis, complications such as fatal visceral, cerebral, and/or retroperitoneal hemorrhage occur with some frequency, resulting in a high-risk benefit ratio for this therapy (Schweizer et al, 2000); therefore, the use of this modality is concerning.…”
Section: Discussionmentioning
confidence: 99%